P26 Inhibition of mitochondrial fission decreased endothelial cell von willebrand factor content and gap junction communication. (21st March 2018) - Kaloya, S; McCarron, J; Chalmers, S; McCormick, C
Abstract : The endothelium is the innermost layer of vascular cells, with a central role in maintaining vascular health. Within endothelial cells, mitochondria play important roles in calcium homeostasis, reactive oxygen species production and, to a lesser extent, ATP generation. The balance of mitochondrial fission, fusion and motility is likely to provide fine control of subcellular location and interactions of the organelle; however, the outcome of perturbation of mitochondrial dynamics on endothelial function remains unclear. We sought to address this gap by investigating the effects of mitochondrial fission inhibitor, Mdivi-1, on endothelial cells. Treatment of cultured endothelial cells with Mdivi-1 (1 or 10 µM, 48 hour) increased mitochondrial length and branching extent compared to control, consistent with inhibition of fission. Mdivi-1 increased branched, twisted and looped endothelial mitochondrial morphologies, whilst also reducing net mitochondrial speed. No acute toxicity was observed after Mdivi-1 treatment (10 µM, 48 hour), however Mdivi-1 did decrease the intracellular content of the glycoprotein von Willebrand Factor (produced, stored and released by endothelial cells to aid thrombosis). Endothelial gap junction communication was also assessed as a function of confluent cells' ability to inter-cellularly transfer the dye, Lucifer yellow; Mdivi-1 decreased dye transfer rates, suggesting reduced intercellular gap junction communication. In conclusion, Mdivi-1 treatment altered endothelial mitochondrial morphology and dynamics, and also decreased von Willebrand Factor content and gap junction communication, however the mechanistic links remain unclear. Clarification is important, as modulation of mitochondrial dynamics has been proposed as a novel target against the cell proliferation associated with vascular disease.